Manipulation of light in plasmonic nano-structures - Abd-Allah, Rehab Kotb (AUC Knowledge Fountain, 2014)
Manipulating light at nano-scale is usually shadowed by the diffraction limit. Recently, plasmonics have emerged as a new technology that enables confining light at nano-scale. Using plasmonic structures, photonic devices can be shrunk from the micro-scale to the nano-scale. In this thesis, a novel structure to a plasmonic nano-filter is introduced and analyzed. The proposed nano-resonator has low loss, compact size and good sensing characteristics. A closed form model to the filter behavior is developed. The model is extracted from the waveguide physical parameters and provides a physical insight into the structure of the filter. An analytical model to the propagation constant and the losses of Metal-Insulator-Metal plasmonic waveguide is proposed. This model is simple, accurate, and shows a good agreement with Finite Difference Time Domain (FDTD) simulations. The model provides a good methodology to obtain high quality filters using cascaded inline filtering. Novel mechanisms for tuning and controlling the response of the plasmonic filter are introduced. These mechanisms allow for full control on the transmission response from these waveguide based structures. This control can be done mechanically, electrically, or optically. Wideband tuning range has been obtained using these schemes. The mechanical tunability is based on changing the filter dimensions using Micro/Nano electro mechanical systems (MEMS/NEMS). The electrical and optical tunability is based on using a nonlinear dielectric material with Pockels or Kerr effect. The tunability is achieved by applying an external voltage or through controlling the input light intensity. The proposed nano-filter supports both red and blue shift in the resonance response. A new approach to control the input light intensity by applying an external voltage to a previous stage is investigated. Tuning the resonance wavelength with high accuracy, minimum insertion loss and high quality factor is obtained using these approaches. The proposed nano-filter can be used in various plasmonic applications such as sensing, biomedical diagnostics and on-chip interconnects. Plasmonic structures can also be used to design nano-optical tweezers. A novel structure for nano optical tweezers using plasmonic triple slit structure is introduced and analyzed. The tweezers have deep potential wells that can trap sub-10-nm dielectric particle stably and efficiently. The resultant 50KT potential well provides tight trapping to the particle. The proposed plasmonic structure allows for steering the particle by simply changing the angle of the incident plane. This simple control allows efficient manipulation to the trapped particle over a wide angle range.